MENINGKATKAN HASIL BELAJAR SISWA SMP MELALUI PENDEKATAN BELAJAR SAINTIFIC PADA MATA PELAJARAN PRAKARYA - Elfrida Saragih (Journal of Social Studies, Arts and Humanities (JSSAH), 2022)
IMPROVING THE LEARNING OUTCOMES OF JUNIOR HIGH SCHOOL STUDENTS THROUGH A SCIENTIFIC LEARNING APPROACH IN CRAFT SUBJECTSThe purpose of this study was to determine the increase in student learning outcomes regarding the Processing of Animal Husbandry and Fishery Products in Craft subjects through the use of a Scientific Learning Approach. This research was conducted in a junior high school (SMP Negeri 19 Bogor City) with the research subjects being students of class IX.F. The method used is a classroom action research method which consists of two cycles. In the first cycle, the learning is carried out using the Scientific Learning Approach, while in the second cycle, the Scientific Learning Approach has been refined. Each cycle consists of four stages of research, namely planning, implementing actions, observing, and reflecting. The research data were analyzed using comparative descriptive followed by reflection. Comparative descriptive is done by comparing the initial condition data, cycle 1 and cycle 2, both for learning outcomes. The results of this study indicate that: First, the use of the Scientific Learning Approach can improve student learning outcomes about the Processing of Foodstuffs from Animal Husbandry and Fisheries in Craft subjects. It is proven that the percentage of student learning outcomes has increased from the initial condition the average daily test score of 63.69 in the first cycle to 72.88 and in the second cycle to 78.16 or in the final condition it increased by 22.7% from the initial condition. . It is proven that the percentage of student learning mastery increases from the initial condition of 64.52% in the first cycle and becomes 93.55% in the second cycle or in the final condition, an increase of 44.99% from the initial condition.